Deep Eutectic Solvents as à-la-Carte Medium for Transition-Metal-Catalyzed Organic Processes - Xavier Marset; Gabriela Guillena (Molecules, 2022)
Our society is facing a tremendous challenge to become more sustainable in every sphere of life. Regarding the chemical industry, one of the most significant issues to be addressed is the use of volatile organic compounds (VOCs) as solvents because they are petrol-derived and most of them are toxic and flammable. Among the possible solutions, deep eutectic solvents (DESs) have emerged as sustainable alternatives to VOCs in organic catalyzed transformations and other fields. The advantages of these new reaction media are not only related to their more benign physical and chemical properties and, for most of them, their renewable sources but also due to the possibility of being recycled after their use, increasing the sustainability of the catalyzed process in which they are involved. However, their use as media in catalytic transformations introduces new challenges regarding the compatibility and activity of known catalysts. Therefore, designed catalysts and “à-la-carte” DESs systems have been developed to overcome this problem, to maximize the reaction outcomes and to allow the recyclability of the catalyst/media system. Over the last decade, the popularity of these solvents has steadily increased, with several examples of efficient metal-catalyzed organic transformations, showing the efficiency of the catalysts/DES system, compared to the related transformations carried out in VOCs. Additionally, due to the inherent properties of the DES, unknown transformations can be carried out using the appropriated catalyst/DES system. All these examples of sustainable catalytic processes are compiled in this review.